S Sosialisasi Dampak Pernikahan Dini: Membangun Kesadaran Masyarakat Desa Plerean Kabupaten Jember: Socialisation of the Impact of Early Marriage: Building Community Awareness in Plerean Village, Jember - Mutmainnah, Mutmainnah; Agustin, Erninda Puji; Wardana, Hengky (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
This community service activity aimed to raise awareness among the residents of Plerean Village, Sumberjambe District, Jember Regency about the negative impacts of early marriage. The socialization was conducted by participants of the 2024 Jember Collaborative Kuliah Kerja Nyata (KKN), from the Office of Religious Affairs (KUA) as the main speaker. Through lectures and interactive discussions, the material covered the definition of early marriage, the reasons behind it, its negative impacts, relevant laws and policies, and the Islamic perspective on the ideal age for marriage. The results showed a significant increase in the community’s understanding of the risks associated with early marriage and the importance of delaying marriage until a mature age is reached. Pre- and post-test results showed that participants' understanding of the detrimental effects of early marriage had increased by 30%. Up to 60% of individuals declared their intention to stop getting married young, demonstrating a favorable shift in mindset. Community support for the initiative was reinforced by a 20% increase in the involvement of community leaders. In addition, there was a commitment from 45% of participants to discourage early marriage in their families. Continuous education and socialization were found to be effective in reducing the incidence of early marriage in Plerean Village